Alternative method to evaluate performance improvement rate in athletics middle distance events - Barbosa, L. P.; Santos, P. A.; Aguiar, S. S.; Simões, H. G.; Nikolaidis, P. T.; Knechtle, B.; Sousa, C. V. (Journal of Science in Sport and Exercise, 2022)
Purpose: The aims of this study were to propose an alternative method to assess an optimal performance improvement rate (PIR) that would be used as a tool for coaches and elite athletes willing to reach their personal best, mainly those seeking for national, continental or even world record (WR) in middle-distance events. We further compared the improvement rate of women vs. men of the top-10 ranked athletes in the IAAF running these middle-distance events Method: The top 10 athletes in the IAAF ranking of 800 m, 1500 m, and 3000 m events for each sex were assessed for their history of race times before achieving their personal record (PR). The difference between PR (`actual` season) and the best race time in the last season was defined as the 1st season improvement rate (1-SIR), whereas the average improvement rate in the last and preceding seasons was the multi-season improvement rate (M-SIR). 1-SIR and M-SIR were calculated for each athlete. Result: There were sex differences in the 1500 m with a large effect size (d = - 0.746) in 1-SIR (P = 0.001) and very large (d = - 2.249) in M-SIR (P = 0.001). Women improved more than men before the PR/WR achievements in the 800 m and 1500 m events (P = 0.001) and had similar improvement rates before performing PR/WR in 3000 m events (P = 0.533). Conclusion: Women improve more before PR/WR achievement in 800 m and 1500 m races. However, in the 3000 m men and women have similar improvement rates in previous seasons before the PR/WR achievement.